Pelaksanaan Perlindungan Pekerja Migran Indonesia Menurut Undang-Undang Nomor 18 Tahun 2017 Tentang Perlindungan Pekerja Migran Indonesia: (Studi BP2MI Lombok Barat) - Gumilang Rustamaji; Rahmawati Kusuma (Fakultas Hukum Universitas Mataram, 2023)
This research aimed to find out the protection effort for Indonesian migrant workers by BP2MI of the West Lombok regency according to Law number 18 of 2017 concerning protection for Indonesian migrant workers. This research can be categorized as normative-empirical legal research. It can be concluded that the government has implemented this law by providing attendance for future migrant workers. It is also known several other implementations have been in accordance with the provisions of Law number 18 of 2018 concerning the protection of Indonesian migrant workers.